Underdiagnosis of Rickettsiosis in Primary Health Care Facilities: A Cross-sectional Study in Jakarta, Indonesia - Aiman Idrus Alatas; Delly Chipta Lestari; Khie Chen Lie; Dewi Lokida; Suratno Lulut Ratnoglik (Journal of Global Antimicrobial Resistance)
AIM: To establish the rate of rickettsiosis among patients presenting acute febrile illnesses at primary healthcare facilities in Jakarta, Indonesia. BACKGROUND: Rickettsiosis is a major public health problem in Indonesia. Though they are found in many different areas and have great clinical significance, there is a limited diagnostic capacity for human rickettsiosis particularly at the primary care level. Since its symptoms can resemble those of other causes of acute fever, failure to diagnose rickettsiosis could lead to severe outcomes, including neurological complications, multi-organ dysfunction, and many more. METHODS: A total of 50 subjects with acute febrile illness from three primary health centers were involved in this cross-sectional study. Blood collected from patients was retrospectively analyzed for rickettsiosis using Immunofluorescence Assay (IFA) IgM and polymerase chain reaction (PCR). The distribution of rickettsiosis was further stratified by age, laboratory findings, and initial diagnosis. RESULTS: Among these 50 patients, seven were diagnosed with rickettsiosis based on blood work (IFA IgM: 5; PCR: 1; both: 1). Surprisingly, none of these individuals had initially been thought to have rickettsial infections. The infected population consisted mainly of adults (6 out of 7). Four rickettsiosis patients were initially diagnosed with typhoid fever, one with an upper respiratory tract infection, and two with nonspecific fever. Routine blood tests showed normal white blood cell counts in all cases. CONCLUSIONS: These findings show the considerable underreporting of rickettsiosis in primary health care centers in Jakarta. It is important to enhance awareness and diagnostic capacity to prevent underdiagnosis and associated complications.